Next practices: Innovations in the COVID-19 social protection responses and beyond - Maya Hammad; Fabianna Bacil; Fabio Veras Soares (International Policy Centre for Inclusive Growth (IPC-IG), 2021)
The COVID-19 pandemic has necessitated large-scale, rapid responses from governments to ensure that the negative effects of the crisis on people's livelihoods are mitigated. Countries with more well-established social protection systems in place prior to the crisis were able to respond faster, but almost all countries required innovative practices to quickly deliver social protection to those usually excluded from benefits, such as informal-sector workers, refugees and migrants. This paper aims to systematise the social protection innovations implemented in response to the COVID-19 crisis, which can be leveraged to build more inclusive and sustainable systems in the medium and long term.
Keywords: 330; social protection; COVID-19; missing middle; policy innovation